The effects of a high protein diet on indices of health and body composition – a crossover trial in resistance-trained men. Issue 1 (December 2016) - Antonio, Jose; Ellerbroek, Anya; Silver, Tobin; Vargas, Leonel; Peacock, Corey
Abstract Background Eight weeks of a high protein diet (>3 g/kg/day) coupled with a periodized heavy resistance training program has been shown to positively affect body composition with no deleterious effects on health. Using a randomized, crossover design, resistance-trained male subjects underwent a 16-week intervention (i.e., two 8-week periods) in which they consumed either their normal (i.e., habitual) or a higher protein diet (>3 g/kg/day). Thus, the purpose of this study was to ascertain if significantly increasing protein intake would affect clinical markers of health (i.e., lipids, kidney function, etc.) as well as performance and body composition in young males with extensive resistance training experience. Methods Twelve healthy resistance-trained men volunteered for this study (mean ± SD: age 25.9 ± 3.7 years; height 178.0 ± 8.5 cm; years of resistance training experience 7.6 ± 3.6) with 11 subjects completing most of the assessments. In a randomized crossover trial, subjects were tested at baseline and after two 8-week treatment periods (i.e., habitual [normal] diet and high protein diet) for body composition, measures of health (i.e., blood lipids, comprehensive metabolic panel) and performance. Each subject maintained a food diary for the 16-week treatment period (i.e., 8 weeks on their normal or habitual diet and 8 weeks on a high protein diet). Each subject provided a food diary of two weekdays and one weekend day per week. In addition, subjects kept a diary of their training regimen that was used to calculate total work performed. Results During the normal and high protein phase of the treatment period, subjects consumed 2.6 ± 0.8 and 3.3 ± 0.8 g/kg/day of dietary protein, respectively. The mean protein intake over the 4-month period was 2.9 ± 0.9 g/kg/day. The high protein group consumed significantly more calories and protein (p  < 0.05) than the normal protein group. There were no differences in dietary intake between the groups for any other measure. Moreover, there were no significant changes in body composition or markers of health in either group. There were no side effects (i.e., blood lipids, glucose, renal, kidney function etc.) regarding high protein consumption. Conclusion In resistance-trained young men who do not significantly alter their training regimen, consuming a high protein diet (2.6 to 3.3 g/kg/day) over a 4-month period has no effect on blood lipids or markers of renal and hepatic function. Nor were there any changes in performance or body composition. This is the first crossover trial using resistance-trained subjects in which the elevation of protein intake to over four times the recommended dietary allowance has shown no harmful effects.